Postmodern youth ministry : exploring cultural shift, cultivating authentic community, creating holistic connections - Jones, Tony, 1968- (Grand Rapids, MI : Zondervan, 2001)
Includes bibliographical references.
Keywords: Church work with youth; Postmodernism -- religious aspects -- Christianity